Retrospective analysis of the efficacy and safety of anlotinib plus sintilimab (anti-PD-1) as maintenance therapy in advanced pediatric solid tumors - Zhao, Rui; Chang, Luyang; Zhang, Chengyi; He, Rongheng; Wei, Xudong (Frontiers in Oncology, 2025)
BackgroundAdvanced solid tumors in children have limited maintenance treatment options. This study assessed the effectiveness and safety of anlotinib in conjunction with sintilimab as maintenance therapy for advanced pediatric solid tumors in real-world settings.MethodsThis single-institution retrospective study was conducted at the Affiliated Cancer Hospital of Zhengzhou University from November 2019 to October 2023. Forty-six patients with advanced pediatric solid tumors who achieved partial response or stable disease following first-line (22/46) or second-line (24/46) chemotherapy subsequently received maintenance therapy with a combination of anlotinib and sintilimab. The primary endpoint was median progression-free survival (mPFS). Secondary endpoints included median overall survival (mOS), disease control rate (DCR), and safety.ResultsAfter a median follow-up of 21.8 months (95% CI, 16.5–27.1), the mPFS was 25.3 months (95% CI, 7.0–43.6) in the first-line treatment group and 13.3 months (95% CI, 7.2–19.4) in the second-line treatment group. The mOS in the first-line and second-line treatment groups was 38.2 months (95% CI, 22.2–54.1) and 16.5 months (95% CI, 12.6–20.4), respectively. The DCR was 50.0% (11/22; 95% CI, 28–72) in the first-line group and 37.5% (9/24; 95% CI, 19–59) in the second-line group. Most treatment-related adverse events were grade 1–2. The most common grade 3–4 adverse event was anemia (2/46, 4.3%).ConclusionThese results indicate that maintenance therapy using anlotinib combined with sintilimab could be a safe and effective treatment option for advanced pediatric tumors.